The Moderating Role of Work Discipline in the Training–Performance Relationship - I Made Aryata; I Gede Marenrda (LPPM STIE KRAKATAU, 2026)
This study aims to analyze the effect of training on employee performance and examine the role of work discipline as a moderating variable. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method, which allows for simultaneous testing of structural relationships between latent variables and provides more accurate estimates by testing measurement and structural models. In this study, the training variable was tested on Employee Performance with training as a moderating variable using the SEM method. The research sample consisted of 185 respondents selected to represent the study population. The results showed that training had no significant effect on employee performance, with β=0.167 and p = 0.235, indicating that training could not been able to directly improve performance. Conversely, work discipline has a positive and significant effect on employee performance, with a p-value of 0.000, indicating that the level of compliance with work rules and standards plays an important role in increasing productivity and performance quality. Furthermore, the results of the moderation test showed that work discipline strengthened the effect of training on employee performance, with β=-0.019 and a p-value of 0.004. This finding indicates that the effectiveness of training is highly dependent on employees work discipline. One of the main limitations lies in the scope of the variables used, as other factors can influence employee performance. Therefore, further research is recommended to develop a research model by adding other relevant variables.